Hubungan tingkat kebutuhan perawatan ortodonti menggunakan index of orthodontic treatment need (iotn) dengan dental aesthetic index (dai) - Riko Nofrizal; Cecillia Virgina Maharani (Jurnal Kedokteran Gigi Terpadu, 2023)
Background: Malocclusion occurs due to a change in dimensions from primary teeth to permanent teeth. The most common malocclusion in children aged 9-11 years is caused by the eruption of the canines and second premolars, requiring orthodontic treatment. To be able to determine the level of need for orthodontic treatment, an orthodontic index is needed, one of which is the Index Of Orthodontic Treatment Need (IOTN) and the Dental Aesthetic Index (DAI). The orthodontic clinic at RSGM-P FKG Trisakti University is a clinic that performs interceptive orthodontic treatment in the mixed dentition period. The aim of this study was to determine the correlation between the level of need for orthodontic treatment using the Index Of Orthodontic Treatment Need (IOTN) and the Dental Aesthetic Index (DAI) on patients aged 9-11 years at the orthodontic clinic of the RSGM-P FKG Trisakti University. Methods: The research method used was an analytic observational study with a cross-sectional study design. Results: The results of the research based on the results of the Spearman's rho correlation test, obtained a significance value of 0.905 (sig <0.05), the strength of the relationship of 0.023 means that the correlation is very weak between variables. Conclusion: So that it can be concluded that there is no significant relationship between the need for orthodontic treatment based on IOTN and DAI in patients aged 9-11 years at RSGM-P FKG Trisakti University.